Bycatch Incidence in Artisanal Fisheries of Cameroon, West Africa - I, Ayissi; TJE, Jiofack (Contemporary Research and Perspectives in Biological Science Vol. 11, 2025)
By-catch is a common threat to marine fauna such as mammals and reptiles. The by-catch assessment has been carried out along the Cameroon coastline to map artisanal fishing effort and quantify the impact of by-catch on sea turtles and marine mammals during three months from June to September 2011, and specific objectives include: To interview fishermen in various fishing villages or ports in Cameroon regarding fishing effort and catch. To estimate the fishing gears used in these fishing ports. To evaluate the impacts of by-catch on marine mammals and sea turtles. In total, 30 fishing ports were been planned, but 23 were covered with 932 files in total (245 long forms and 685 short forms). In total, 4121 boats (none motorized and motorized) and the common gears used are gillnet and surround seine. The results reveal that, yearly, around 1228 turtles with a back (green, hawksbill and olive) were caught and 13. Leatherback; most not intentionally. But in the Sandje port, the intentional catch by local fishermen with around 400 individuals per year for international commercial uses is noted. These numbers are low according to certain data on sea turtle surveys along the Cameroon coast. About cetaceans and manatees, the following data are 97 and 292, respectively, for each group, but most manatees are caught intentionally for the bush meat trade. The survey was limited in time and lacked baseline information on the issue, but in the future, it could be good to involve more permanent data collectors and scientific observers. These results must be feedback to official services for good monitoring of marine fauna and their ecosystem.